Evaluación de la relación precipitación escorrentía de largo plazo en la cuenca del Río Geul (2004)
The river Geul is a tributary o/ the river Meuse and its catchment area (340 km2) is partlylocated in Belgium and the south o/ The Netherlands. The Geul connects with the Meuse sornekilometres north o/the city o/Maastricht. During heavy rain/all, the river ofien floods causinggreat damage. This situation may be aggravated by changes in land use and climate. During thepast 50 years, the population more than doubled, urbanisation was rapid, watercourses were modified, land use was changed, and heavy agricultural machinery was introduced. AII oftheseaspects may have contributed to a change in the hydrological regime of the catchment. Anassessment ofthe long-term rainfall-runoffre/ation was carried out by jirst, deriving a reliabletime series ofabout 50 years ofdaily discharges for the Geul rivel: Following this, an analysis ofthe homogeneity ofand detection ofpossiblejumps in the precipitation, evaporation and dischargetime series was pe,formed. A study ofthe rainfall-runoff re/ation was then can'ied out using alumped conceptual mode/ cal/ed HAM. Finally, the water balance of the catchment wasinvestigatedfor a possible change in its components over the last 50years. Tltis study shows thatcontrary to recent publications and public opinion, the peak discharges ofthe Geul in Meerssenhave not increased. The annual volume ofrunofffrom the catchment ofthe Geulshows a decreasingtrend indicating "water loss //, It is therefore recommended fa investigate the possible cause ojthese losses from the catchment ofthe Geul.